Defining Smart City. A Conceptual Framework Based on Keyword Analysis - Mosannenzadeh, Farnaz; Vettorato, Daniele (TeMA - Journal of Land Use, Mobility and Environment, 2014)
“Smart city” is a concept that has been the subject of increasing attention in urban planning and governance during recent years. The first step to create Smart Cities is to understand its concept. However, a brief review of literature shows that the concept of Smart City is the subject of controversy. Thus, the main purpose of this paper is to provide a conceptual framework to define Smart City. To this aim, an extensive literature review was done. Then, a keyword analysis on literature was held against main research questions (why, what, who, when, where, how) and based on three main domains involved in the policy decision making process and Smart City plan development: Academic, Industrial and Governmental. This resulted in a conceptual framework for Smart City. The result clarifies the definition of Smart City, while providing a framework to define Smart City’s each sub-system. Moreover, urban authorities can apply this framework in Smart City initiatives in order to recognize their main goals, main components, and key stakeholders.